Effects of food supply and stream physical characteristics on habitat use of a stream‐dwelling fish. Issue 1 (16th February 2017) - Akbaripasand, Abbas; Closs, Gerard P.
Abstract: Identifying the environmental factors that affect freshwater fish can be crucial for their conservation and management. Despite the widespread investigation of relationships between fish habitat use and environmental variables, there is a paucity of knowledge on how abiotic and biotic factors jointly influence stream fish habitat use. Three New Zealand South Island streams were selected to investigate the habitat preference of a stream‐dwelling galaxiid, banded kokopu ( Galaxias fasciatus ). Fish abundance in several permanent pools was determined by spotlighting at night once a month from June 2008 to May 2009. Drifting invertebrates and key physical features of each pool were measured at the time of fish sampling. An information‐theoretic approach (AIC) indicated that the most parsimonious candidate model to predict banded kokopu biomass was the one that included pool area, undercut banks, water velocity, overhanging vegetation, invertebrate drift density and an interaction term between invertebrate drift density and water velocity. Banded kokopu biomass was positively related to pool area, undercut banks, overhanging vegetation and invertebrate drift density. Our study suggests that fish resource use patterns need to be understood in the context of multiple interacting ecological factors, including prey abundance.